2011
DOI: 10.5296/ijhrs.v1i1.851
|View full text |Cite
|
Sign up to set email alerts
|

Performance Appraisal Systems In Public Sector Universities Of Pakistan

Abstract: The current research investigates different aspects of performance appraisal system, & how performance appraisal system can play its role in improving the performance of teachers in higher education institutions of Pakistan. In the present study multi-methods approach was used which consist of survey questionnaire and in depth interviews. Survey questionnaire was used in order to investigate various aspects of current performance appraisal system and in depth interview to study the perception of teachers on pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Result of (Figure 1.3) research shows that 26.5% of the employees strongly agree that evaluation methods of PTCL are fair (Mean 4.1), 27.1% of workforce strongly wants feedback on quarterly performance evaluation (Mean 4.2), 27.5% of the employees strongly agree that performance evaluation improve their mistake and give them satisfaction and 24.3% employees really identify gap in performance and appreciate evaluation (Mean 3.3). The finding of this research agreement with the research of (Anjum, A., Yasmeen, K., & Khan, B, 2011) assessment of employees apart from basic salary improves the satisfaction and organizational commitment of employees.…”
Section: Performance Policies and Practicessupporting
confidence: 90%
“…Result of (Figure 1.3) research shows that 26.5% of the employees strongly agree that evaluation methods of PTCL are fair (Mean 4.1), 27.1% of workforce strongly wants feedback on quarterly performance evaluation (Mean 4.2), 27.5% of the employees strongly agree that performance evaluation improve their mistake and give them satisfaction and 24.3% employees really identify gap in performance and appreciate evaluation (Mean 3.3). The finding of this research agreement with the research of (Anjum, A., Yasmeen, K., & Khan, B, 2011) assessment of employees apart from basic salary improves the satisfaction and organizational commitment of employees.…”
Section: Performance Policies and Practicessupporting
confidence: 90%
“…Standard evaluation methods for improvement of performance are typically built on financial standard or built on some indexes which are measured and closely linked with financial performance (Amin & Khan, 2009). Thus, an effective evaluation method shall be a comprehensive evaluation system based on multiple angles (Anjum et al, 2011). The performance assessment system has many different roles here.…”
Section:  mentioning
confidence: 99%
“…A number of studies focused on aspects of effective performance appraisals [2], and how appraisal processes likely influence academics' performance [3]. The importance of performance appraisal has been addressed by numerous authors, identified potentially as a key tool of performance management for both university management and academics [4]. When designed and implemented appropriately, performance appraisals arguably may identify and evaluate performance of individual faculty member, provide incentives and outline professional development opportunities, and monitor the progress of the institution toward attaining its goals and objectives [5].…”
Section: Introductionmentioning
confidence: 99%